Publicness in times of market accountability: Lessons from a changing hospital industry in Germany. (January 2019) - Bode, Ingo
Drawing on findings from a multiple case study on the changing hospital industry in Germany, this article sheds fresh light on the implications new public management-driven regulatory frameworks may have regarding the 'publicness' of public service settings. It is shown that, in the area under study, key ingredients of the settings' traditional mission persist, as do expectations towards soci(et)al effectiveness of actual service delivery. However, this is paralleled by the rise of market accountability within and around these settings which undergirds the 'privateness' of public-service providing undertakings. Hydrid accountability relations coincide with a new organisational settlement which leads to a fuzzy configuration regarding the role of publicness. This is why a consistent reinvention of the latter is unlikely to occur under a regulatory framework featuring non-statutory and competitive public service provision.